Revealing Silences: Voiceless Traces of Gendered Trauma in Female Holocaust Survivors’ Writing - Miñano Mañero, Laura (International Journal of English Studies, 2024)
This paper intends to unravel the nexus between sexual violence and silence in textual and figurative silence in female Holocaust survivors’ writing. I will argue that these tropes allow authors to acknowledge and explore the nature of a gender-specific trauma. The sources under examination encompass Ruth Klüger (2001), Gisella Perl (1948), Judith Magyar-Isaacson (1990), Judith Dribben (1970) and Elzbieta Ettinger (1986), whose works significantly delve into these unspoken realms. I suggest that the tension between the endured sexual violence and the challenges of bearing witness to it is mirrored in these silences, which are infused with narrative strategies that gender the Shoah, illustrate embodied experience and reclaim the victim’s agency. Though feminist Holocaust scholarship has recently turned its focus to the study of sexual violence, its imbrication with silence merits further scrutiny. My approach provides a new framework to stimulate this discussion by igniting the reflection on literary silences.